Delegation of the Creation of Fees to Administrative Entities by the Congress of the Republic (2017)
With the French Revolution one of the major contributions that is enshrined in the tripartite theory of power is identified, which identified the work of the State in three branches: Executive, Legislative, and Judicial; Based on the Legislative Power represented by the Congress of the Republic, the Political Constitution of Colombia of 1991 in its article 150 empowers him to make the Laws; However if it is true that all the taxes that exist in the country are ordered by the law, the Congress begins to question that if its task is to legislate, it can ́t descend to the technical field as it is the case of the creation of rates in the entities Administrative, but that means that through an operative event they can create their own rates. For this reason and through the issuance of Law 399 of 1997, the administrative entity (Invima) is authorized to structure its cost system and set its own rates.